Health Risks Associated with Microphone Sharing: A Survey of Awareness, Perception and Preventative Actions among Christian Church Choir Members in Taraba State, North-East, Nigeria - Idi, Shadrach (Darul Yasin Al Sys, 2024)
The aim of this study was to investigate the awareness and health actions related to the risks of microphone sharing among Christian choir members in Taraba State, Nigeria. Grounded in the Health Belief Model, the study utilised a descriptive survey design, sampling 225 choir members from 10 randomly selected churches across Taraba State, Northeast Nigeria. Data were collected via online questionnaires and analysed using simple descriptive statistics. The findings reveal a low level of awareness about the health risks associated with sharing microphones. The respondents generally demonstrated a negative perception towards these risks, with many expressing disbelief in the potential for disease transmission through shared microphones. Additionally, there was a notable lack of adherence to precautionary measures. The study found that microphones were infrequently cleaned, microphone foams were rarely replaced, and hand hygiene practices—such as hand washing and the use of sanitiser—were not routinely observed. The use of face masks and shields among choir members was also reported as rare. These findings have significant implications for public health practices within religious communities. They underscore the urgent need for increased awareness and education about the potential health risks of microphone sharing. Thus, the study recommends implementing regular cleaning protocols, ensuring the replacement of microphone foams, and promoting personal hygiene measures, including hand sanitisation and the use of face masks or shields during group singing activities. These measures are essential for mitigating health risks and ensuring the well-being of choir members.